Standard operating procedure for paediatric inpatient care in a public general hospital in rural South India: a quality improvement project - Dhali, Arkadeep; D'Souza, Christopher (International Journal Of Community Medicine And Public Health, 2021)
Background: The paediatrician stationed in a Public General Hospital noticed a significant number of complaints from the patient party about the delay in initial assessment and the quality of care provided in the hospital. This initiated the idea to review the standard of care given in the paediatric inpatient ward. Methods: Aiming to ensure proper management of children in the paediatric inpatient ward, a team was formed to improve inpatient care and daily functioning of the ward. A standard operating procedure (SOP) was formulated referring to the National Rural Health Mission (NRHM), while modifying it to suit available resources and manpower in the hospital. A series of interventions were implemented and assessed using plan-do-study-act (PDSA) cycles. The findings from the PDSA cycle of a previous intervention were used to implement change in the next intervention. The data was analysed to accept the change or to further modify it. Results: At the end of 3 months, improvement was noted with the increase in the bed occupancy rate by 22%, paediatric admission rate by 8%, bed turnover rate by 24%, percentage of new-borns exclusively breastfed from admission to discharge by 30%, and proportion of mothers given effective nutritional counselling by 35%. There was also decrease in the time taken for initial assessment by 50 minutes, average length of stay by 2 days and LAMA rate by 4%. Conclusions: In the span of few months, we were able to implement an SOP and bring a significant improvement in the quality of care provided.